The Relationship Between Polyunsaturated Fatty Acid (PUFA) Intake and Cognitive Function in Psychiatric Patients with Depressive Disorders - Erlansa Budiyoga; Linda Kartikasari; Natalia Dewi Wardani (Green Publisher Indonesia, 2026)
Disturbance depressive is a mental health disorder that is often associated with cognitive decline. Nutrition, particularly polyunsaturated fatty acid (PUFA) intake, is thought to play a role in maintaining brain health and cognitive function. However, evidence of a link between PUFA intake and cognitive function as measured by the Montreal Cognitive Assessment (MoCA), Indonesian version (MoCA-Ina), in patients with depressive disorders remains limited. This study aims to evaluate the relationship between PUFA intake and cognitive function in psychiatric patients with depressive disorders. This was an analytical study using secondary data from patients with depressive disorders at Dr. Kariadi General Hospital, Diponegoro National Hospital, Banyumanik Hospital 1, and Elisabeth Hospital Semarang from May 2022 to 2023. The study included patients aged 18–60 years who were diagnosed with depressive disorders, had completed the Food Frequency Questionnaire (FFQ) and MoCA-Ina assessments, and had no serious physical illness or metabolic syndrome. The analysis used the Spearman correlation test to assess the relationship between PUFA intake and cognitive function, as well as the Mann–Whitney test for comparisons based on PUFA intake categories. A total of 30 patients with depressive disorders were included, of whom 83.3% were female, with a mean age of 26.03 years. The mean PUFA intake was 6.31 grams, and the mean MoCA-Ina score was 27.67. The Spearman test showed no significant association between PUFA intake and cognitive function (p = 0.790). There was no significant relationship between PUFA intake and cognitive function in patients with depressive disorders.